A case of giant peripheral osteoma in the maxilla. Issue 5 (September 2022) - Yanai, Yuta; Kubota, Yasutaka; Yanai, Risa; Kozuma, Ayako; Yamada, Tomohiro; Mori, Yoshihide
Abstract: An osteoma is a benign tumor consisting of a proliferation of mature bone. The osteomas are categorized as per their origin into peripheral and central. Peripheral osteoma is a rare entity originating from the periosteum. Peripheral osteomas are found in areas, such as the paranasal sinuses and mandible, but rarely occur in the maxilla. Herein, we describe a case of giant peripheral osteoma that developed in the maxilla and then grew to such an extent that it became difficult for the patient to masticate. The patient was a 61-year-old woman who visited our hospital complaining of a painless mass on her palate that gradually increased in size starting from 15 years ago. A bone-like hard mass with a major axis of approximately 65 mm was found covering the entire palate. The tumor was pedunculated and the base was at the alveolar crest of the maxillary molars. The computed tomography findings showed a well-defined mass surrounded by cortical bone, with a mixture of internal cortical bone-like and cancellous or spongy bone-like parts. A biopsy was performed, and the diagnosis of osteoma was confirmed. Tumor resection was then performed. The size of the resected specimen was 67 × 58 × 29 mm. Histopathologically, it was classified as a cancellous osteoma and was finally diagnosed as peripheral osteoma. The patient was observed for 1 year following the operation and no recurrence was observed.